Lone mothers and poverty in Italy, Germany and Great Britain: evidence from panel data - Elisabetta Ruspini (University of Essex, Institute for Social and Economic Research (ISER), 1999)
This paper focuses on lone mothers poverty in the Italian familistic welfare regime. In order to appreciate its peculiarities, the study of the Italian case will be developed comparatively by taking into account two other European settings, characterised by strong diversities in the resource distribution systems (family, labour market and welfare) and by a different consistence of female economic deprivation: Germany and Great Britain. The data used to analyse lone mothers poverty dynamics are household panel surveys. Introducing a temporal element can substantially increase the explanatory power of empirical analysis: when individuals are surveyed at successive points in time, then it is possible to investigate how individual responses are related to the earlier circumstances, allowing an explanation of change.
Keywords: 330